The effects of soil pollution and its relation with morbidity in shoreline areas - Lourenço, Roberto Wagner [UNESP]; Roveda, S. R M M [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, L. F. [UNESP]; Ribeiro, A. Í [UNESP]; Martins, A. C G [UNESP]; Donalisio, M. R.; Cordeiro, R. (WITPRESS LTD., 2010)
Soil and subsoil pollution is not only significant in terms of environmental loss, but also a matter of environmental and public health. Solid, liquid and gaseous residues are the major soil contamination agents. They originate from urban conglomerates and industrial areas in which it is impossible to emphasize the chemical, petrochemical and textile industry; thermoelectric, mining, and ironmaster activities. The contamination process can thus be defined as a compound addition to soil, from what qualitative and or quantitative manners can modify soil's natural characteristics and use, producing baneful and deteriorative effects on human health. Studies have shown that human exposition to high concentration of some heavy metals found on soil can cause serious health problems, such as pulmonary or kidney complications, liver and nervous system harm, allergy, and the chronic exposition that leads to death. The present study searches for the correlation among soil contamination, done through a geochemical baseline survey of an industrial contamination area on the shoreline of Sao Paulo state. The study will be conducted by spatial analysis using Geographical Information Systems for mapping and regression analysis. The used data are 123 soil samples of percentage concentration of heavy metals. They were sampled and spatially distributed by geostatistics methods. To verify if there is a relation between heavy metals soil pollution and morbidity an executed correlation and regression analysis will be done using the pollution registers as the independent variables and morbidity as dependable variables. It is expected, by the end of the study, to identify the areas relation between heavy metals soil pollution and morbidity, moreover to be able to provide assistance in terms of new methodologies that could facilitate soil pollution control programs and public health planning. © 2010 WIT Press.
Keywords: GIS; Heavy metals; Risk analysis; Soil pollution; Spatial analysis; concentration (composition); health geography; health impact; health risk; heavy metal; industrial waste; morbidity; pollution effect; pollution exposure; public health; risk assessment; soil pollution; spatial analysis; Brazil; Sao Paulo [Brazil]